Tear Proteins Calcium binding protein A4 (S100A4) and Prolactin Induced Protein (PIP) are Potential Biomarkers for Thyroid Eye Disease. Issue 1 (December 2018) - Chng, Chiaw-Ling; Seah, Lay; Yang, Morgan; Shen, Sunny; Koh, Siew; Gao, Yan; Deng, Lu; Tong, Louis; Beuerman, Roger; Zhou, Lei
Abstract There are no reliable biomarkers to predict thyroid eye disease (TED) in patients with autoimmune thyroid disease (AITD) currently. Several evidences support the involvement of the lacrimal gland in TED. The aim of our study was to quantitatively correlate the changes in tear protein profile with increasing severity of TED. Tear samples were collected from four groups of patients; AITD without TED (AITD), AITD with mild TED (mild TED), AITD with severe TED (severe TED) and normal controls. A total of 72 patients were recruited for the study. In discovery phase, isobaric tags for relative and absolute quantification (iTRAQ) 4-plex was used for quantitative proteomics analysis. For verification of results from discovery phase, sequential window acquisition of all theoretical fragment ion spectra (SWATH) was used to analyze an independent cohort from normal controls, AITD, mild TED and severe TED. Two proteins, S100A4 and PIP showed consistent dysregulation trends in the discovery and validation phase experiments. Our study demonstrated the differences in tear proteome across the spectrum of different severity and activity of TED in patients with AITD. Two tear proteins, S100A4 and PIP may serve as potential biomarkers to predict progression to severe TED in patients with AITD.